(untitled) - Tesla, Nikola (Stelle, Illinois, 1993)
This book chronologically traces the original intention that Nikola Tesla had for his wireless electricity and how he updated and expanded upon it later on, with reprints of his key articles, to the recent genius engineers and physicists who are now finally bringing this last and most elusive, highly advanced Tesla technology into reality.
Keywords: Nhà phát minh,Inventors; Tiểu sử,Biography; Hòa Kỳ,United States